A Evolução das Colaborações Científicas no WebMedia: Um Estudo de 15 Anos (2010-2024) - Nunes, Gabriel Victor Vieira; Marques, Gabriel Azevedo; Santos, Samuel Souza; Santos, Octávio Augusto dos; Bianch, Samuel Oliveira Silva; Oliveira, Fábio Henrique M.; Aranha, Renan Vinicius; Vieira, Vinícius da Fonseca; Silva, João Gabriel Rocha (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2025: Proceedings of the 31st Brazilian Symposium on Multimedia and the WebDO - 10.5753/webmedia.2025.16095, 2025)
This work presents a bibliometric and social network analysis applied to the study of scientific collaborations at the Brazilian Symposium on Multimedia and theWeb (WebMedia) over a fifteen-year period (2010–2024). Using data extracted from the Brazilian Computer Society platform, the study investigates the dynamics of interinstitutional partnerships, the temporal evolution of co-authorship networks, and the distribution of scientific production among different institutions. Through the construction of collaboration networks, analyzed using structural metrics and visualizations, it was possible to identify a pattern of strong concentration of production within a restricted group of institutions, while simultaneously observing increasing national integration and diversification of the actors involved. Furthermore, it was found that a few institutions are responsible for the majority of scientific production, highlighting the need to consider strategies and policies that encourage the participation and strengthening of other institutions, thereby expanding collaboration and fostering a more balanced and inclusive scientific environment.